Method for manufacturing electrode active material comprising ternary sulfide for lithium secondary battery, electrode active material for lithium secondary battery manufactured thereby and lithium secondary battery including the same

A mechanical energy-based method efficiently synthesizes Fe2GeS4 compounds for lithium secondary batteries, enhancing battery performance by improving cycle life and capacity through a simple and efficient manufacturing process.

KR103044226B1Active Publication Date: 2026-11-05국립금오공과대학교산학협력단
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020230049412
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2026-11-05
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

Existing methods for manufacturing Fe2GeS4 compounds are complex and inefficient, hindering the development of secondary battery systems using this compound as an electrode active material.

Method used

A simple and efficient method involving mechanical energy application to a mixed powder of transition metal, metalloid, and sulfur powders to synthesize Fe2GeS4, followed by heat-treatment with graphene oxide to form a composite, using high-energy ball milling and reducing gas atmosphere.

Benefits of technology

Enables the production of Fe2GeS4 compounds suitable for lithium secondary batteries with excellent cycle life, high initial efficiency, and capacity, while minimizing degradation and improving mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112023042340710-PAT00009_ABST
    Figure 112023042340710-PAT00009_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing an electrode active material for a lithium secondary battery, comprising the steps of: (a) manufacturing a mixed powder of a transition metal powder, a metalloid powder, and sulfur (S) powder; and (b) applying mechanical energy to the mixed powder to synthesize an olivine orthorhombic ternary sulfide represented by A2BS4 (where A is a transition metal element selected from the group consisting of Fe, Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Y, Zr, Nb, and Mo, and B is a metalloid element selected from the group consisting of Ge, Al, Si, Ga, In, and Sn); an electrode active material for a lithium secondary battery manufactured thereby; and a lithium secondary battery comprising the same. The olivine orthorhombic ternary sulfide, particularly the ternary Fe2GeS4 compound manufactured by the method according to the present invention, has excellent initial efficiency and charge and discharge characteristics, and is therefore suitable for use as an electrode active material for a lithium secondary battery, particularly a Li||Fe2GeS4 secondary battery system. Li||Fe2GeS4 secondary battery systems containing ternary Fe2GeS4 compounds also have excellent cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing an electrode active material for a lithium secondary battery, an electrode active material for a lithium secondary battery manufactured thereby, and a lithium secondary battery comprising the same. Background Technology

[0002] Maintaining the structure of pyrite (FeS) and a high light absorption coefficient (>10 5 cm -1 Ternary Fe2GeS4 compounds, which exhibit ) and possess appropriate bandgap (1.40 eV) characteristics, are receiving great attention in the field of optical energy materials.

[0003] Fe2GeS4, which has an olivine A2BX4 orthorhombic crystal structure in the space group Pnma, maintains a three-dimensional olivine A2BX4 orthorhombic crystal structure in which S atoms form a hexagonal closed-packed structure, Fe atoms occupy half of the octahedral coordination, and Ge atoms occupy 1 / 8 of the tetrahedral coordination.

[0004] Meanwhile, the aforementioned ternary Fe2GeS4 compound is known only to be manufactured through complex and inefficient processes, such as high-cost chemical synthesis methods using conventional precursor solutions or long-duration vacuum heat treatment synthesis methods; therefore, there is a need to develop a simpler and more efficient manufacturing method. Furthermore, there is a requirement for the development of technology to design various secondary battery systems based on secondary battery voltage design using electrodes made of the aforementioned ternary Fe2GeS4 compound. Prior art literature

[0005] J. Am. Chem. Soc.2020, 142, 15, 7023-7035 The problem to be solved

[0006] The objective of the present invention is to provide an electrode active material for a lithium secondary battery comprising a transition metal-metal sulfide, such as an olivine orthorhombic structure Fe2GeS4 compound, manufactured using a simple and efficient method without undergoing complex and inefficient processes such as conventional chemical methods.

[0007] In addition, the present invention aims to provide a lithium secondary battery system comprising an electrode active material for the lithium secondary battery through voltage design of the secondary battery system. means of solving the problem

[0008] The present invention, for solving the above problem, provides a method for manufacturing an electrode active material for a lithium secondary battery comprising the steps of: (a) manufacturing a mixed powder of a transition metal powder, a metalloid powder, and sulfur (S) powder; and (b) synthesizing an olivine orthorhombic ternary sulfide represented by the following chemical formula by applying mechanical energy to the mixed powder.

[0009] [Chemical Formula]

[0010] A2BS4

[0011] (In the above chemical formula,

[0012] A is a transition metal element selected from the group consisting of Fe, Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Y, Zr, Nb and Mo, and

[0013] B is a metalloid element selected from the group consisting of Ge, Al, Si, Ga, In, and Sn.

[0014] In addition, a method for manufacturing an electrode active material for a lithium secondary battery is provided, characterized by applying mechanical energy to a high-energy spex mill, a vibrotary-mill, a Z-mill, a planetary ball-mill, or an attrition-mill in step (b).

[0015] In addition, the present invention provides a method for manufacturing an electrode active material for a lithium secondary battery, characterized by comprising the steps of: (a) preparing a mixed powder of iron (Fe) powder as a transition metal powder, germanium (Ge) powder and sulfur (S) powder as metalloid powders; and (b) synthesizing Fe2GeS4 by applying mechanical energy to the mixed powder.

[0016] At this time, a method for manufacturing an electrode active material for a lithium secondary battery is provided, characterized by manufacturing a ternary Fe2GeS4 compound powder having an average diameter of 1 nm or more and 500 μm or less in step (b).

[0017] In addition, the present invention provides a method for manufacturing an electrode active material for a lithium secondary battery, characterized by further including, as a step (c) following step (b) above, a step of heat-treating a mixture of olivine orthorhombic ternary sulfide and graphene oxide (GO) in a reducing gas atmosphere to produce a composite of olivine orthorhombic ternary sulfide and reduced graphene oxide (rGO).

[0018] In addition, a method for manufacturing an electrode active material for a lithium secondary battery is provided, characterized by heat-treating a mixture of Fe2GeS4 and graphene oxide (GO) in a reducing gas atmosphere in step (c) to produce a composite (Fe2GeS4-rGO) of Fe2GeS4 and reduced graphene oxide (rGO).

[0019] In addition, in another aspect of the invention, the present invention provides an electrode active material for a lithium secondary battery comprising an electrode active material comprising a ternary sulfide prepared by the above-described manufacturing method.

[0020] In addition, in another aspect of the invention, the present invention provides a lithium secondary battery comprising the electrode active material.

[0021] In addition, as an example of the above-mentioned lithium secondary battery, a lithium secondary battery is provided having a positive electrode comprising a positive electrode comprising a positive electrode active material comprising a ternary sulfide Fe2GeS4 and a negative electrode comprising a lithium metal.

[0022] In addition, as another example of the sodium secondary battery, a lithium secondary battery is provided having a negative electrode comprising Fe2GeS4-rGO, which is a composite of Fe2GeS4 and reduced graphene oxide (rGO).

[0023] Furthermore, in another aspect of the invention, the present invention relates to a Li-capacity curve plotted with respect to voltage (V) for a first charge / discharge cycle of the lithium secondary battery, derived from a curve plotting the derivative (dQ / dV) of the voltage (V)-capacity (Q) curve according to voltage (V). x A method for driving a lithium secondary battery is provided, characterized by driving the lithium secondary battery in a voltage region between a reaction potential at which a Fe2GeS4 (0 < x ≤ 3) phase is formed and a reaction potential at which a Fe2GeS4 phase is formed. Effects of the invention

[0024] According to the method for manufacturing an electrode active material for a lithium secondary battery according to the present invention, an electrode active material for a lithium secondary battery containing a ternary sulfide such as Fe2GeS4 can be manufactured simply and efficiently by using ball milling, a simple solid synthesis method, without undergoing complex and inefficient processes such as chemical methods.

[0025] In addition, when the ternary Fe2GeS4 compound produced by the above manufacturing method is used as an electrode active material for a lithium secondary battery, a secondary battery system having excellent cycle life while maintaining high initial efficiency and capacity can be realized. Brief explanation of the drawing

[0026] FIG. 1 is a process flow diagram describing the steps of a method for preparing a ternary Fe2GeS4 compound with an olivine orthorhombic structure according to the present invention in sequential order. FIG. 2 is a schematic diagram of a secondary battery system comprising a ternary Fe2GeS4 compound with an olivine orthorhombic structure according to the present invention as an electrode active material. FIG. 3 is a schematic diagram of a secondary battery electrode comprising a ternary Fe2GeS4 compound with an olivine orthorhombic structure according to the present invention as an electrode active material. FIG. 4 is a schematic diagram of the crystal structure of a ternary Fe2GeS4 compound with an olivine orthorhombic structure according to the present invention. Figures 5a and 5b are graphs showing the X-ray diffraction analysis characteristics and X-ray absorption spectroscopy characteristics of the ternary Fe2GeS4 compound with an olivine orthorhombic structure prepared in Example 1 of the present invention, respectively. Figure 6 is a graph showing the charge / discharge test results and cycle characteristics of a half lithium secondary battery containing a ternary Fe2GeS4 compound with an olivine orthorhombic structure prepared in Example 1 of the present invention as a negative electrode active material. Figure 7 is a capacitance derivative curve obtained by differentiating the voltage with respect to the capacitance to observe in more detail the charging and discharging behavior of the first cycle of the tercomponent Fe2GeS4 compound with an olivine orthorhombic structure prepared in Example 1 of the present invention. Figure 8 is a graph showing the charge / discharge test results and cycle characteristics of a lithium secondary battery system containing a ternary Fe2GeS4 compound with an olivine orthorhombic structure prepared in Example 1 of the present invention as a positive electrode active material. FIG. 9 is a schematic diagram of the manufacturing process showing the Fe2GeS4-rGO composite in Example 2 of the present invention. Figures 10a and 10b are graphs showing the X-ray diffraction analysis characteristics and Raman absorption spectroscopy characteristics of the Fe2GeS4-rGO composite prepared in Example 2 of the present invention, respectively. Figure 11 is a graph showing the charge / discharge test results and cycle characteristics of a half lithium secondary battery containing the Fe2GeS4-rGO composite prepared in Example 2 of the present invention as a negative electrode active material. Figure 12 is a graph showing the charge / discharge test results and cycle characteristics of a lithium-ion secondary battery system containing the Fe2GeS4-rGO composite prepared in Example 2 of the present invention as a negative electrode active material. Specific details for implementing the invention

[0027] In describing the present invention, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted.

[0028] Since embodiments according to the concept of the present invention may be subject to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in this specification or application. However, this is not intended to limit embodiments according to the concept of the present invention to specific disclosed forms, and it should be understood that they include all modifications, equivalents, and substitutions that fall within the spirit and scope of the present invention.

[0029] The terms used herein are used merely to describe specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as “comprising” or “having” are intended to specify the existence of the described features, numbers, steps, actions, components, parts, or combinations thereof, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0030] The present invention will be described in detail below.

[0031] A method for manufacturing an electrode active material for a lithium secondary battery according to the present invention comprises: (a) a step of manufacturing a mixed powder of a transition metal powder, a metalloid powder and a sulfur (S) powder; and (b) a step of synthesizing an olivine orthorhombic ternary sulfide represented by the following chemical formula by applying mechanical energy to the mixed powder.

[0032] [Chemical Formula]

[0033] A2BS4

[0034] (In the above chemical formula,

[0035] A is a transition metal element selected from the group consisting of Fe, Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Y, Zr, Nb and Mo, and

[0036] B is a metalloid element selected from the group consisting of Ge, Al, Si, Ga, In, and Sn.

[0037] For example, a method for manufacturing an electrode active material for a lithium secondary battery according to the present invention may include, as illustrated in FIG. 1, a step of (a) manufacturing a mixed powder of iron (Fe) powder, germanium (Ge) powder and sulfur (S) powder, and a step of (b) synthesizing a ternary Fe2GeS4 compound by applying mechanical energy to the mixed powder.

[0038] At this time, step (a) above is a step of preparing a mixed powder by mixing iron (Fe) powder, germanium (Ge) powder, and sulfur (S) powder, which are starting materials for the preparation of a compound. It is preferable to mix the weight ratios of each starting material to match the stoichiometry of the compound to be finally synthesized, and the method used to prepare the mixed powder in this step is not particularly limited as long as it is a method that can uniformly mix each starting material.

[0039] In step (a), the iron (Fe) powder, germanium (Ge) powder, and sulfur (S) powder are not affected by product purity, and it is desirable to consider the effect of moisture when preparing the ternary Fe2GeS4 compound.

[0040] Next, in step (b), mechanical energy is applied to the mixed powder obtained in the previous step to induce an alloying reaction in the combination of (Fe) powder, germanium (Ge) powder, and sulfur (S) powder to produce a ternary Fe2GeS4 compound with an olivine orthorhombic crystal structure.

[0041] Mechanical energy is applied to a mixed powder containing transition metallic iron (Fe), metallometallic germanium (Ge) powder and nonmetallic sulfur (S) powder using high energy mechanical milling (HEMM) to induce a total alloying reaction between the transition metallic iron (Fe), metallometallic germanium (Ge) powder and nonmetallic sulfur (S) powder to obtain a ternary sulfide with an olivine orthorhombic structure, and this process can be expressed by the following reaction equation 1.

[0042] <Reaction Equation>

[0043] 2Fe + Ge + 4S → Fe2GeS4

[0044] Referring to the above reaction equation, a ternary Fe2GeS4 compound with an olivine orthorhombic structure can be prepared by inducing an alloying reaction after adding transition metallic iron (Fe), metalloid germanium (Ge) powder, and non-metallic sulfur (S) powder using a ball milling solid synthesis method. In particular, by using a simple ball milling manufacturing method to induce the alloying reaction of the ternary sulfide, the ternary Fe2GeS4 compound can be prepared simply and efficiently without performing conventional chemical synthesis methods.

[0045] In step (b), the method of applying mechanical energy to the mixed powder comprising transition metallic iron (Fe), metalloid germanium (Ge) powder and non-metallic sulfur (S) powder is not particularly limited, but it is preferable to use high-energy ball milling for the alloying reaction of the ternary sulfide.

[0046] The above high-energy ball milling can be performed by any known ball milling device used for high-energy ball milling, such as a vibrotary-mill, Z-mill, planetary ball-mill, or attrition-mill. For reference, in a typical high-energy ball milling process, the temperature can rise to 200°C during ball milling, and the pressure can also be on the order of 6 GPa.

[0047] As described above, by using a solid-state synthesis method utilizing high-energy ball milling, ternary Fe2GeS4 compounds with an olivine orthorhombic structure can be prepared simply and efficiently without performing conventional chemical synthesis methods. Meanwhile, a more specific method for preparing ternary Fe2GeS4 compounds with an olivine orthorhombic structure according to the present invention through a solid-state synthesis method utilizing high-energy ball milling is as follows.

[0048] First, uniformly mixed powders of transition metallic iron (Fe), metalloid germanium (Ge), and non-metallic sulfur (S) are loaded into a cylindrical vial along with balls and mounted in a high-energy ball milling machine, and then mechanical synthesis is performed at a rotational speed of 500 to 2000 revolutions per minute to produce ternary iron germanium sulfide (Fe2GeS4). The ball milling can be performed for 1 to 24 hours. Here, the weight ratio of balls to the mixture is maintained, for example, at 10:1 to 30:1, and the mechanical synthesis is prepared in a glove box under an argon gas atmosphere to minimize the influence of oxygen and moisture.

[0049] The ternary sulfide produced by the above-described manufacturing method, in particular, the ternary Fe2GeS4 compound having an olivine orthorhombic structure, is suitable for use as a negative electrode active material for lithium-ion secondary batteries because it possesses excellent initial efficiency and charge / discharge characteristics. Furthermore, it is suitable for use as a positive electrode active material for lithium Fe2GeS4 secondary batteries by controlling the operating voltage range of the battery. In particular, the cycle life of the lithium Fe2GeS4 secondary battery containing the above-described ternary Fe2GeS4 compound is also excellent.

[0050] Meanwhile, the above ternary Fe2GeS4 compound preferably has a powder form with an average diameter of 1 nm or more and less than 500 μm, and preferably has low crystallinity.

[0051] Furthermore, the present invention provides a lithium secondary battery comprising an electrode active material prepared according to the present invention, such as a ternary Fe2GeS4 compound having an olivine orthorhombic structure.

[0052] FIG. 2 is a schematic diagram of a lithium secondary battery system comprising an electrode active material prepared according to the present invention, such as a ternary Fe2GeS4 compound with an olivine orthorhombic structure.

[0053] The above lithium secondary battery (1) may include a first electrode (11), a second electrode (12), and a separator (13) disposed between the first electrode (11) and the second electrode (12). The above secondary battery (1) may further include an electrolyte (not shown), a battery container (14), and a sealing member (15) that encloses the battery container (14). Such a secondary battery (1) may be manufactured by stacking the first electrode (11), the second electrode (12), and the separator (13) in sequence, and then storing them in the battery container (14) in a wound state.

[0054] FIG. 3 is a schematic diagram of a lithium secondary battery electrode comprising an electrode active material prepared according to the present invention, such as a ternary Fe2GeS4 compound with an olivine orthorhombic structure.

[0055] The first electrode (11) may include a current collector (111) and an active material layer (112) formed on the current collector (111). The active material layer (112) includes an electrode active material such as a ternary Fe2GeS4 compound manufactured according to the present invention. The first electrode (11) may additionally include a water-insoluble binder such as polyvinylidene fluoride (PVdF) or a water-soluble binder such as polyethyleneimine, polyaniline, polythiophene, polyacrylic acid (PAA), carboxymethylcellulose (CMC), or styrene-butadiene lever (SBR).

[0056] Meanwhile, in the present invention, when using the lithium secondary battery system, it is desirable to adjust the potential range of the battery to maintain high capacity while ensuring a stable lifespan by charging and discharging multiple cycles.

[0057] At this time, in the above potential region, Li in the capacity differential curve of the first cycle x By adjusting the reaction potential from the reaction potential at which the Fe2GeS4 phase is formed to the reaction potential at which the Fe2GeS4 phase is formed, the crystal structure becomes stable, and as can be seen in the first embodiment below, a stable lifespan can be secured by charging and discharging in multiple cycles while maintaining a high capacity.

[0058] Embodiments of the present invention are described below. However, the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete and to sufficiently convey the concept of the present invention to those skilled in the art.

[0059] <Example 1>

[0060] (1) Olivine orthorhombic structure ternary Fe using mechanical alloying 2 GeS 4 Preparation of compounds

[0061] Iron (Fe) powder, germanium (Ge) powder, and sulfur (S) powder were mixed in a molar ratio of 2:1:4, loaded into a cylindrical vial of SKD11 material with a diameter of 5.5 cm and a height of 9 cm along with 3 / 8-inch balls, mounted on a ball mill (spex 8000), and mechanical synthesis was performed at a rotational speed of 900 revolutions per minute.

[0062] At this time, the weight ratio of balls to powder was maintained at 20:1, and mechanical synthesis was prepared in a glove box under an argon gas atmosphere to minimize the influence of oxygen and moisture. Fe2GeS4 was prepared by performing the above mechanical synthesis for 6 to 12 hours.

[0063] For reference, Figure 4 is a schematic diagram showing the crystal structure of Fe2GeS4 with an olivine orthorhombic structure synthesized above.

[0064] Figure 5a is a graph showing the X-ray diffraction analysis characteristics of a ternary Fe2GeS4 compound with an olivine orthorhombic structure, and Figure 5b is a graph showing the X-ray absorption spectroscopy (EXAFS) characteristics of a ternary Fe2GeS4 compound with an olivine orthorhombic structure. The synthesized ternary Fe2GeS4 compound with an olivine orthorhombic structure can be easily synthesized in a form ranging from tens of nanometers to several nanometers.

[0065] (2) Olivine ternary Fe with orthorhombic structure 2 GeS 4 Evaluation of charge and discharge capacity, initial efficiency, and cycle characteristics of compounds and lithium-ion secondary batteries containing them

[0066] Figure 6 is a graph showing the results of an electrochemical charge-discharge experiment of a half-lithium-ion secondary battery of a ternary Fe2GeS4 compound with an olivine orthorhombic structure. The graph shows the charge and discharge behavior for the 1st, 2nd, 5th, and 10th cycles, respectively, when using the ternary Fe2GeS4 compound. When using the ternary Fe2GeS4 compound, the charge and discharge capacities of the 1st cycle were 1079 mAh / g and 848 mAh / g, respectively, in the lithium-ion secondary battery system, and the efficiency of the initial cycle was about 79%.

[0067] Figure 7 shows the capacity derivative curve of the first cycle to observe in more detail the reaction between the ternary Fe2GeS4 compound of the first embodiment, prepared through mechanical alloying, and lithium. Referring to Figure 7, at 1.3 V, Li x It can be seen that the Fe2GeS4 phase is formed, where x represents 0 to 3 moles of lithium. Furthermore, as the potential decreases further, ultimately Li 3.75 Ge and Li2S It can be seen that a phase is formed. Furthermore, it can be seen that the Fe2GeS4 phase is formed at 2.5 V.

[0068] FIG. 8 shows the case where the ternary Fe2GeS4 compound of the first embodiment, prepared through mechanical alloying, is applied as the positive active material of a Li||Fe2GeS4 secondary battery system, Li x The graph shows the charge and discharge cycle characteristics for the potential range (1.3–2.5 V) from the reaction potential at which the Fe2GeS4 phase is formed to the reaction potential at which the Fe2GeS4 phase is formed. As can be seen from Fig. 8, Li x For the potential range from 1.3 V, the reaction potential for forming the Fe2GeS4 phase, to 2.5 V, the reaction potential for forming the Fe2GeS4 phase, 550 mAh / cm² 3It can be seen that it exhibits very stable cycle characteristics of at least 100 cycles while maintaining a high capacity of over 100 cycles.

[0069] <Example 2>

[0070] (1) Olivine orthorhombic structure ternary Fe using mechanical alloying 2 GeS 4 Preparation of a composite of a compound and reduced graphene oxide (rGO)

[0071] Iron (Fe) powder, germanium (Ge) powder, and sulfur (S) powder were mixed in a molar ratio of 2:1:4, loaded into a cylindrical vial of SKD11 material with a diameter of 5.5 cm and a height of 9 cm along with 3 / 8-inch balls, mounted on a ball mill (spex 8000), and mechanical synthesis was performed at a rotational speed of 900 revolutions per minute.

[0072] At this time, the weight ratio of balls to powder was maintained at 20:1, and mechanical synthesis was prepared in a glove box under an argon gas atmosphere to minimize the influence of oxygen and moisture. Fe2GeS4 was prepared by performing the above mechanical synthesis for 6 to 12 hours.

[0073] The prepared Fe2GeS4 was added to distilled water and uniformly dispersed using a sonicator for 2 to 4 hours, then polyethyleneimine (PEI, polyethylenimine) was added to the Fe2GeS4 dispersion solution and stirred at 25 to 27 ℃ for 12 hours.

[0074] The above stirred solution was added to a graphene oxide (GO) solution and stirred at 25–27°C for 6 hours, after which the powder mixed with Fe2GeS4 and GO was recovered using a centrifuge at a rotation speed of 4,000 revolutions per minute.

[0075] The above powder mixed with Fe2GeS4 and GO was heat-treated at 600°C for 2 hours in an atmosphere of a gas mixture of hydrogen and argon (6% H2+ 94% Ar) to reduce GO and produce an Fe2GeS4-rGO composite.

[0076] For reference, Fig. 9 is a schematic diagram showing the process of preparing a composite of the olivine orthorhombic structure Fe2GeS4 compound prepared above and reduced graphene oxide (rGO).

[0077] Figure 10a is a graph showing the X-ray diffraction analysis characteristics of the Fe2GeS4-rGO composite prepared above, and Figure 10b is a graph showing the Raman absorption spectroscopy characteristics of the Fe2GeS4-rGO composite prepared above. The prepared Fe2GeS4-rGO composite can be easily synthesized in the form of Fe2GeS4 compounds ranging in size from tens of nanometers to several nanometers on reduced graphene oxide.

[0078] (2) Fe 2 GeS 4 Evaluation of charge and discharge capacity, initial efficiency, and cycle characteristics of rGO composites and lithium-ion secondary batteries containing the same

[0079] Figure 11 is a graph showing the results of electrochemical charge-discharge experiments on a half-lithium-ion secondary battery of the Fe2GeS4-rGO composite. The graph above shows Fe2GeS 4- This is a graph showing the charge and discharge behavior for the 1st, 2nd, 5th, 10th, 20th, 30th, 40th, 50th, and 100th cycles, respectively, when using an rGO composite. Fe2GeS 4- In the case of using an rGO composite, the charge and discharge capacities of the first cycle were 1065 mAh / g and 730 mAh / g, respectively, in the lithium-ion secondary battery system, and the efficiency of the initial cycle was about 69%.

[0080] Figure 12 is a graph of the experimental results of the electrochemical charge-discharge cycle characteristics of the Fe2GeS4-rGO composite prepared above. In the case of using the Fe2GeS4-rGO composite, very stable cycle characteristics were exhibited while maintaining a high capacity of 812 mAh / g up to the 200th cycle.

[0081] As described above, the present invention uses a ternary Fe2GeS4 compound with an olivine orthorhombic structure as a cathode material for a lithium secondary battery, particularly a Li||Fe2GeS4 secondary battery system. In this case, the problem of degradation in lifespan characteristics caused by the electrolyte leaching of sulfur (S) from the cathode material and the shuttle effect occurring in the cathode of the lithium secondary battery system can be minimized by manufacturing the ternary Fe2GeS4 compound.

[0082] Accordingly, mechanical stability, which is considered most important in the cathode of lithium secondary batteries, particularly Li||Fe2GeS4 secondary battery systems, can be secured, and capacity and cycle life can also be improved. Furthermore, Li||Fe2GeS4 secondary battery systems utilizing the above-mentioned ternary Fe2GeS4 compound with an olivine orthorhombic structure exhibit high capacity and excellent cycle characteristics.

[0083] Although embodiments of the present invention have been described above with reference to the attached drawings, those skilled in the art will understand that the present invention may be implemented in other specific forms without changing its technical concept or essential features. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. Explanation of the symbols

[0084] 1: Secondary battery 11: First electrode 12: Second electrode 13: Separator 14: Battery container 15: Encapsulating member 111: Entire house 112: Active material layer

Claims

Claim 1 A method for manufacturing an electrode active material for a lithium secondary battery, comprising: (a) a step of preparing a mixed powder of iron (Fe) powder, germanium (Ge) powder and sulfur (S) powder; (b) a step of synthesizing Fe2GeS4 by applying mechanical energy to the mixed powder; and (c) a step of preparing a composite (Fe2GeS4-rGO) of Fe2GeS4 and reduced graphene oxide (rGO) by heat-treating a mixture of Fe2GeS4 and graphene oxide (GO) in a reducing gas atmosphere, wherein in step (b), mechanical energy is applied using a high-energy spex mill, a vibrotary mill, a Z-mill, a planetary ball mill, or an attrition mill. Claim 2 delete Claim 3 delete Claim 4 A method for manufacturing an electrode active material for a lithium secondary battery, characterized in that, in step (b) of claim 1, Fe2GeS4 powder having an average diameter of 1 nm or more and 500 μm or less is manufactured. Claim 5 delete Claim 6 delete Claim 7 An electrode active material for a lithium secondary battery comprising a ternary sulfide manufactured by the manufacturing method of claim 1 or 4. Claim 8 A lithium secondary battery comprising an electrode active material according to paragraph 7. Claim 9 delete Claim 10 A lithium secondary battery having a negative electrode comprising an Fe2GeS4-rGO composite in claim 8. Claim 11 delete

Citation Information

Patent Citations

  • Lithium ion battery cathode material Fe2SiS4 and composite material Fe2SiS4 / CPAN thereof

    CN106025224A

  • Method for manufacturing layered ternary compounds, electrode materials for secondary battery manufactured thereby and secondary battery including the same

    KR102490533B1

  • Electronic cell with a non-aqueous electrolyte

    US4381258A